Pengembangan Media Pembelajaran Komik Digital (KODIG) pada Elemen Pemahaman IPAS pada Fase B - Winna Rahmayani; H. Syahrilfuddin; M. Jaya Adi Putra (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to increase students' reading material about photosynthesis and utilise technology by developing digital comic-based learning media entitled "What is Photosynthesis". This comic is designed in digital form to be easily accessible without cost. Media development uses the R&D (Research & Development) method and the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted at SD Negeri 188 Pekanbaru in the even semester of the 2023/2024 academic year involving students in grades IV A and IV B. The data was collected through a questionnaire with two questionnaires. Data were collected through questionnaires with two trials, namely small group trials and 1:1 trials. Validation by media experts involved six aspects: cover, opening page, word balloons, background, language use, and material, with all aspects getting a very valid category (87.5%-100%). Implementation involved 10 students in a small group trial (average result 98%) and 4 students in a 1:1 trial (average result 99%). Two grade IV teachers were also involved with an average result of 99%. These results show that the digital comic "What is Photosynthesis" is very feasible to use as a learning media in schools.